FROM THEORY TO PRACTICE: A FRAMEWORK FOR COMMUNICATIVE PROJECT-BASED LEARNING (CPBL) IN TECHNICAL ENGLISH EDUCATION - Nazarov Rustam Irkinovich (Western European Studies, 2025)
While the need for enhanced communicative competence among engineering students is widely acknowledged, the practical question of how to effectively cultivate these skills within a technical curriculum remains a significant challenge. This paper addresses this gap by proposing and illustrating a detailed pedagogical methodology: Communicative Project-Based Learning (CPBL). The CPBL framework moves beyond traditional teaching methods by centering the learning experience around authentic, complex engineering projects. Within this framework, English is not taught as a separate subject but is used as a functional tool for research, collaboration, problem-solving, and presentation. The article outlines the core principles of CPBL—language integration, authenticity, collaboration, and formative assessment—and provides a step-by-step guide for its implementation. To demonstrate its practical application and effectiveness, the paper presents a detailed case illustration of a "Sustainable Energy Solution" project, mapping specific project stages to the language and communication skills being developed. The findings suggest that CPBL is a highly effective, motivating, and holistic methodology for preparing engineering students for the real-world communication demands of their future careers
Keywords: project-based learning; communicative competence; technical English